Illustrated C# 7 The C# Language Presented Clearly, Concisely, and Visually - Solis, Daniel (Apress, 2018)
Get to work quickly with C# with a uniquely succinct and visual format used to present the C# 7.0 language. Whether you're getting to grips with C# for the first time or working to deepen your understanding, you'll find this book to be a clear and refreshing take on each aspect of the language. Figures are of prime importance in this book. While teaching programming seminars, Daniel Solis found that he could almost watch the light bulbs going on over the students' heads as he drew the figures on the whiteboard. In this text, he has distilled each important concept into simple but accurate illustrations. For this latest edition, Dan is joined by fellow experienced teacher and programmer, Cal Schrotenboer, to bring you the very latest C# language features, along with an understanding of the frameworks it most often lives in: .NET and the new .NET Core. For something as intricate and precise as a programming language, there must be text as well as figures. But rather than long, wordy explanations, the authors use short, concise descriptions and bullet lists to make each important piece of information visually distinct and memorable. What You'll Learn: Start with an overview of C# programming and how the language works under the hood Put things in context with a little useful history of C# and .NET Know how .NET Core fits into the picture Understand how C# handles types Benefit from clear, concise explanations of each language feature, from classes and inheritance to enumerators and iterators, and the new C# 7.0 tuples Quickly access material via this book's visual introduction to asynchronous programming with C#.